2013
DOI: 10.1245/s10434-013-3408-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Breast Lymphedema

Abstract: Introduction The development of breast lymphedema (BLE) following breast/axillary surgery is poorly characterized. We prospectively evaluated clinical and surgical factors associated with development of BLE. Methods Patients undergoing unilateral breast-conserving surgery were prospectively enrolled preoperatively and followed for development of BLE. To augment the number of patients with BLE for evaluation of risk factors, postoperative patients identified in the clinic with signs and symptoms of BLE were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 15 publications
(24 reference statements)
0
35
0
2
Order By: Relevance
“…Risk factors include removal of more than five axillary lymph nodes, obesity, and axillary radiation therapy. [39][40][41][42] Although traditional clinical guidelines for patients at risk of developing breast cancer-related lymphedema included postoperative restrictions on upper body activity, recent studies have demonstrated that upper body strength training is not only safe but appears to reduce the risk of postoperative breast cancer-related lymphedema. 43 Thus, the inclusion of a graduated weight-training program after the initial mastectomy and reconstruction is a crucial part of the postoperative regimen for patients undergoing axillary lymph node dissection to optimize lymphatic drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors include removal of more than five axillary lymph nodes, obesity, and axillary radiation therapy. [39][40][41][42] Although traditional clinical guidelines for patients at risk of developing breast cancer-related lymphedema included postoperative restrictions on upper body activity, recent studies have demonstrated that upper body strength training is not only safe but appears to reduce the risk of postoperative breast cancer-related lymphedema. 43 Thus, the inclusion of a graduated weight-training program after the initial mastectomy and reconstruction is a crucial part of the postoperative regimen for patients undergoing axillary lymph node dissection to optimize lymphatic drainage.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to congratulate Dr. Giacalone, Dr. Yamamoto and colleagues on a very well written and interesting article (Giacalone & Yamamoto, 2017) that brings into attention one surprisingly neglected aspect of the secondary breast lymphedema in cancer therapy. As stated from our colleagues, breast lymphedema is a not seldom occurrence after breast conserving therapy and axillary lymphnode dissection (Boughey et al, 2014;Degnim et al, 2012). In the case of extremity lymphedema, conservative treatment represents the first line of therapy.…”
mentioning
confidence: 72%
“…In the USA and other parts of the developed world, malignancy and its treatment, including surgery and radiation, are the most common secondary causes of lymphedema . Additionally, elements, such as obesity, extent of axillary surgery, radiotherapy, infection, and trauma, have been identified as factors predisposing to lymphedema .…”
Section: Current Systems For Staging Lymphedemamentioning
confidence: 99%